2021
DOI: 10.3390/jcm10102069
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-Free Anesthesia Benefit–Risk Balance: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Opioid-free anesthesia (OFA) is used in surgery to avoid opioid-related side effects. However, uncertainty exists in the balance between OFA benefits and risks. We searched for randomized controlled trials (RCTs) comparing OFA to opioid-based anesthesia (OBA) in five international databases. The co-primary outcomes were postoperative acute pain and morphine consumption at 2, 24, and 48 h. The secondary outcomes were the incidence of postoperative chronic pain, hemodynamic tolerance, severe adverse effects, opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 56 publications
1
40
0
1
Order By: Relevance
“…However, a lower opioid request was registered in the opioid-inclusive strategy group [ 22 ]. On the contrary, Salome et al found that OFA is associated with a reduction in the pain score at 2 h [−0.75 (−1.18, −0.32)], followed by reduction in morphine administration at 2 and 24 h after surgery [MD: −1.61 (−2.69, −0.53) and −1.73 (−2.82, −0.65) ( p < 0.05)] [ 23 ]. Similarly, also Fletcher described a decreased opioid consumption and postoperative pain at 24 h in the OFA group [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a lower opioid request was registered in the opioid-inclusive strategy group [ 22 ]. On the contrary, Salome et al found that OFA is associated with a reduction in the pain score at 2 h [−0.75 (−1.18, −0.32)], followed by reduction in morphine administration at 2 and 24 h after surgery [MD: −1.61 (−2.69, −0.53) and −1.73 (−2.82, −0.65) ( p < 0.05)] [ 23 ]. Similarly, also Fletcher described a decreased opioid consumption and postoperative pain at 24 h in the OFA group [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis, including 33 RCTs and 2209 participants, showed no clinically significant benefits in terms of pain and opioid use after surgery, but a clear benefit with respect to a reduction in PONV was demonstrated when intraoperative opioids were avoided [37]. In a previous meta-analysis and systematic review of 23 trials, Frauenknecht et al reported that OFA did not reduce pain scores after surgery, but it was associated with a decreased rate of PONV with a risk ratio of 0.77 (95%CI (0.61-0.97), p = 0.03) [14].…”
Section: Discussionmentioning
confidence: 99%
“…8 In two meta-analyses, patients receiving OFA had a lower incidence of PONV than those receiving opioid-based anesthesia but had similar postoperative pain scores. 9 , 10 In another meta-analysis, OFA significantly reduced adverse postoperative events with significantly lower postoperative opioid consumption. 11 However, the literature on OFA is still controversial because some studies that have not shown benefits 12 , 13 or worse outcomes.…”
Section: Introductionmentioning
confidence: 97%